Legal Review of Traffic Violations by Motorcyclists in Urban Areas - Amalia Tasya (Ipso Jure, 2024)
Traffic violations by motorcyclists are a serious problem that often occurs in urban areas and contribute to high accident rates and congestion. This article examines the legal aspects of these violations by examining the applicable legal provisions, especially in Law Number 22 of 2009 concerning Traffic and Road Transportation (LLAJ Law), and evaluating the effectiveness of its law enforcement. This study uses a normative legal method and is supported by empirical data from the Traffic Police regarding the most common types of violations in big cities such as Jakarta and Surabaya. The results show that although legal sanctions have been regulated, weak law enforcement and low public legal awareness are the main obstacles. A more humanistic and educative approach is needed in the implementation of traffic law enforcement.